Is informal sector work an alternative to workfare benefits? The case of pre-program expansion and economic crisis - Melanie Khamis (Institute for the Study of Labor (IZA), 2009)
Limited availability of workfare programs and unemployment insurance and a large informal sector are features of the Argentine labor market at the outset of the 2001 economic crisis. This paper tests the hypothesis whether informal work is an alternative to workfare participation before a large-scale program expansion took place. Results from the propensity score matching indicate that observable characteristics of informal low-income workers and current workfare participants are significantly different. However, within these groups, it is possible to identify subgroups that exhibit similar observable characteristics. This indicates that only a subset of the individuals sees workfare and informal sector work as substitutable alternatives.
Keywords: J42; J48; O17; 330; South America; Argentina; informal labor market; workfare program; propensity score matching; Aktivierende Sozialhilfe; Schwarzarbeit; Schattenwirtschaft; Substitutionseffekt; Schätzung; Argentinien